Secondary battery and device

By using nitrite additives in lithium-ion batteries, the wetting property of the electrolyte and the stability of the solid electrolyte interface film are improved, and the insufficient performance of silicon-based materials in lithium-ion batteries is solved, and higher energy density and cycle life are achieved.

CN119674263APending Publication Date: 2025-03-21NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311219442.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the silicon-based materials have poor conductivity, large volume expansion, low cycle life, poor stability and poor rate performance, resulting in the energy density and cycle life that cannot meet high demand.

Method used

Nitrite additives are used as electrolyte components. By adjusting the mass percentage content of the nitrite additive and the compaction density of the negative electrode sheet, the wetting of the electrolyte solution on the electrode surface is improved, and the lithium cyclic evolution is inhibited, and a tough solid electrolyte interface film (SEI) is formed, thereby improving the capacity retention rate and reducing impedance during the cycle.

Benefits of technology

It effectively improves the circulation capacity retention rate of lithium-ion batteries, while reducing impedance during the circulation process, and improving the energy density and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674263A_ABST
    Figure CN119674263A_ABST
Patent Text Reader

Abstract

The invention relates to a secondary battery and an apparatus. The secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the electrolyte comprises a nitrite ester additive as shown in a formula I: # imgabs0 #, in the formula (I), R1 is selected from fluorine substituted or unsubstituted C1-11 alkyl groups, fluorine substituted or unsubstituted C1-8 alkoxy groups, fluorine substituted or unsubstituted C2-6 alkenyl groups, fluorine substituted or unsubstituted C2-6 alkenyloxy groups, fluorine substituted or unsubstituted C2-6 alkynyl groups, fluorine substituted or unsubstituted C2-6 alkynyloxy groups, and fluorine substituted or unsubstituted C3-8 cycloalkyl groups; a fluorine substituted or unsubstituted C3-8 epoxy alkyl group or a fluorine substituted or unsubstituted C6-12 aryl group; based on the mass of the electrolyte, the mass percentage of the nitrite additive is Y%; the compaction density of the negative pole piece is X g / cm < 3 >; wherein-0.4 < = Y-1. 1194 * X < 3 > + 4.0598 * X < 2 >-5.1657 * X + 2.0564 < = 0.4. Therefore, the secondary battery has at least one of the following advantages: relatively high cycle capacity retention rate and relatively low impedance DCR.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of energy storage materials, and in particular to a secondary battery and a device. Background Art

[0002] Lithium-ion batteries are widely used in smart phones, unmanned aerial vehicles, hybrid electric vehicles, etc., but with the development of society, low energy density lithium-ion batteries can no longer meet the demand; the fundamental factor to improve the energy density of lithium-ion batteries is to improve the performance of lithium-ion battery positive and negative electrode materials. In terms of negative electrode materials, the specific capacity of traditional graphite negative electrode materials is close to the theoretical limit (372mAh / g), which is difficult to meet the needs of higher energy density lithium-ion batteries. Therefore, the development of new battery negative electrode materials with higher specific capacity has become an important direction of research and development in this field.

[0003] The theoretical specific capacity of silicon-based materials is as high as 4200mAh / g, and the abundance of silicon in nature is high, and the raw material sources are rich. However, silicon-based materials have the following disadvantages when used as negative electrodes for lithium-ion batteries: silicon-based materials have poor conductivity, silicon-based materials expand by 400% in volume during charge and discharge, and the broken silicon reacts with the electrolyte to produce excessive solid electrolyte interface film (SEI), which leads to low initial coulomb efficiency, low capacity utilization efficiency, low cycle life, poor stability, and poor rate performance of silicon-based batteries. The most effective method at present is to increase the cycle life of silicon-based materials by adding a certain amount of fluoroethylene carbonate (FEC), but FEC has a large viscosity. If FEC is used in large quantities at high compaction density (for example, based on the mass of the electrolyte, the mass percentage of FEC exceeds 5%), it will be difficult for the electrolyte to enter the pores in the negative electrode, resulting in the battery's wettability, cycle life, and film-forming effect being hindered.

[0004] Therefore, finding a silicon negative electrode film-forming additive with a small addition amount and significant effect under high compaction density is of great significance for high energy density silicon-based batteries. Summary of the invention

[0005] In view of the problems existing in the prior art, the present disclosure provides a secondary battery and a device including the secondary battery.

[0006] In a first aspect, the present application provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the electrolyte comprises a nitrite additive as shown in Formula I:

[0007]

[0008] Wherein R1 is selected from fluorine-substituted or unsubstituted C 1-11 Alkyl, fluorine-substituted or unsubstituted C 1-8 Alkoxy, fluorine-substituted or unsubstituted C2-6 Alkenyl, fluorine-substituted or unsubstituted C 2-6 Alkenyloxy, fluorine-substituted or unsubstituted C 2-6 Alkynyl, fluorine-substituted or unsubstituted C 2-6 Alkynyloxy, fluorine-substituted or unsubstituted C 3-8 Cycloalkyl, fluorine-substituted or unsubstituted C 3-8 Oxiranyl or fluorine-substituted or unsubstituted C 6-12 Aryl;

[0009] Based on the mass of the electrolyte, the mass percentage of the nitrite additive is Y%; the compaction density of the negative electrode plate is X g / cm 3 ;

[0010] Where, -0.4≤Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564≤0.4.

[0011] In a second aspect, the present application provides a device, which includes the secondary battery described in the first aspect.

[0012] Beneficial effects of this application:

[0013] In the present application, the nitrite additive can improve the wettability of the electrolyte on the surface of the electrode plate at a higher compaction density, and inhibit the lithium precipitation during the cycle; at the same time, the nitrite additive undergoes reduction decomposition during the cycle process, and decomposes on the negative electrode surface to form a tough solid electrolyte interface film (SEI), which inhibits the rupture of the electrode particles during the cycle and improves the capacity retention rate; and the amount of the nitrite additive can adjust the SEI component on the surface of the negative electrode plate, thereby adjusting the wettability of the surface of the negative active material particles to the electrolyte. By controlling the mass percentage of the nitrite additive and the compaction density of the negative electrode plate, the battery cycle capacity retention rate can be effectively improved, and the impedance DCR during the cycle can be reduced. DETAILED DESCRIPTION

[0014] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present disclosure. The embodiments of the present disclosure should not be interpreted as limiting the present disclosure.

[0015] the term:

[0016] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0017] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0018] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0019] Unless otherwise specified, the terms used in this disclosure have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).

[0020] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values ​​are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values ​​explicitly designated as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.

[0021] A list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0022] The term "C 1-11 The term "alkyl" includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, heptyl, octyl, nonyl, decyl, or undecyl.

[0023] The term "C 1-8 The term "alkoxy" includes, but is not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentoxy, n-hexyloxy, heptyloxy, or octyloxy.

[0024] The term "C 2-6 "Alkenyl" includes but is not limited to ethenyl, propenyl, butenyl, pentenyl or hexenyl, etc.

[0025] The term "C 2-6 "Alkynyl" includes, but is not limited to, ethynyl, propynyl, butynyl, pentynyl or hexynyl, etc.

[0026] The term "C 3-8 "Cycloalkyl" includes, but is not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl or cyclooctyl, etc.

[0027] The term "C 6-12 "Aryl" includes but is not limited to phenyl or naphthyl. Specific implementation method:

[0029] Secondary battery:

[0030] The secondary battery provided in the present application comprises: a positive electrode plate, a negative electrode plate and an electrolyte; the electrolyte comprises a nitrite additive as shown in Formula I:

[0031]

[0032] Wherein R1 is selected from fluorine-substituted or unsubstituted C 1-11 Alkyl, fluorine-substituted or unsubstituted C 1-8 Alkoxy, fluorine-substituted or unsubstituted C2-6 Alkenyl, fluorine-substituted or unsubstituted C 2-6 Alkenyloxy, fluorine-substituted or unsubstituted C 2-6 Alkynyl, fluorine-substituted or unsubstituted C 2-6 Alkynyloxy, fluorine-substituted or unsubstituted C 3-8 Cycloalkyl, fluorine-substituted or unsubstituted C 3-8 Oxiranyl or fluorine-substituted or unsubstituted C 6-12 Aryl;

[0033] Based on the mass of the electrolyte, the mass percentage of the nitrite additive is Y%; the compaction density of the negative electrode is X g / cm 3 ; Among them, -0.4≤Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564≤0.4.

[0034] In the present disclosure, the nitrite additive can improve the wettability of the electrolyte on the surface of the electrode plate at a higher compaction density, and inhibit the lithium precipitation during the cycle; at the same time, the nitrite additive undergoes reduction decomposition during the cycle process, and decomposes on the negative electrode surface to form a tough solid electrolyte interface film (SEI), which inhibits the rupture of electrode particles during the cycle and improves the capacity retention rate; and the amount of the nitrite additive can adjust the SEI component on the surface of the negative electrode plate, thereby adjusting the wettability of the surface of the negative active material particles to the electrolyte. By controlling the mass percentage of the nitrite additive and the compaction density of the negative electrode plate, the battery cycle capacity retention rate can be effectively improved, and the impedance DCR during the cycle can be reduced.

[0035] In some embodiments, Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564 is -0.35, -0.3, -0.25, -0.2, -0.15, -0.1, -0.05, 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or a range consisting of any two of these values. In some embodiments, -0.1≤Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564≤0.1.

[0036] In some embodiments, the compaction density of the negative electrode sheet is X g / cm 3, satisfying: 1.0≤X≤2.6. In some embodiments, X is 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or a range consisting of any two of these values. In some embodiments, 1.4≤X≤2. If the compaction density of the negative electrode plate is too large, the electrolyte / electrode wettability will decrease and the negative electrode particles will break; if the compaction density of the negative electrode plate is too small, the volume energy density of the battery will decrease. In the present application, the compaction density of the negative electrode plate can be adjusted according to the characteristics of the selected negative electrode active material by conventional technical means in the field, such as controlling the rolling pressure, rolling temperature, and rolling speed of the plate.

[0037] In some embodiments, the secondary battery satisfies: 0.01≤Y≤5. In some embodiments, Y is 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or a range consisting of any two of these values. In some embodiments, 0.2≤Y≤3. If the mass percentage of the nitrite additive in the electrolyte is too large, the SEI film will be too thick and the DCR internal resistance will increase in the later stage of the battery cycle; if the mass percentage of the nitrite additive in the electrolyte is too small, the film formation effect will be insufficient and the long-term cycle of the negative electrode particles cannot be protected.

[0038] In some embodiments, R1 is selected from C 1-6 Alkyl, fluorine-substituted or unsubstituted C 1-6 Alkoxy, fluorine-substituted or unsubstituted C 2-6 alkenyl or fluorine substituted or unsubstituted C 6-12 Aryl.

[0039] In some embodiments, the nitrite additive includes at least one of amyl nitrite, ethyl nitrite, propyl nitrite, butyl nitrite, isobutyl nitrite, and hexyl nitrite.

[0040] In some embodiments, the nitrite additive includes amyl nitrite and / or isobutyl nitrite.

[0041] In some embodiments, the electrolyte further comprises a lithium salt, the lithium salt comprising at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorooxalate borate, lithium dioxalate borate, lithium tetrafluoroborate, lithium (trifluoromethylsulfonyl) (perfluorobutylsulfonyl) imide, lithium bis (fluoromalonate) borate, lithium 4,5-dicyano-2-(trifluoromethyl) imidazole and lithium trifluoromethanesulfonate. In some embodiments of the present disclosure, the lithium salt is lithium hexafluorophosphate.

[0042] In some embodiments, the molar concentration of the lithium salt is selected from 0.5 mol / L to 3 mol / L. In some embodiments, the molar concentration of the lithium salt may be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L, but is not limited thereto. In some embodiments, the molar concentration of the lithium salt is 0.5 mol / L to 1.5 mol / L; specifically 0.75 mol / L to 1.25 mol / L, more specifically 1 mol / L.

[0043] In some embodiments, the electrolyte further includes a solvent, the solvent includes at least one of a linear carbonate, a cyclic carbonate and a carboxylic acid ester; the linear carbonate is selected from at least one of dimethyl carbonate, fluorine-substituted dimethyl carbonate, diethyl carbonate, fluorine-substituted diethyl carbonate, dipropyl carbonate, fluorine-substituted dipropyl carbonate, ethyl methyl carbonate, fluorine-substituted ethyl methyl carbonate, methyl propyl carbonate, fluorine-substituted methyl propyl carbonate, ethyl propyl carbonate and fluorine-substituted ethyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluorine-substituted ethylene carbonate, propylene carbonate, fluorine-substituted propylene carbonate, butylene carbonate and fluorine-substituted butylene carbonate; the carboxylic acid ester is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylic acid ester.

[0044] In some embodiments, the solvent includes at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, and diethyl carbonate.

[0045] In some embodiments, the electrolyte further comprises a first additive, the first additive comprising at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate, a silyl-containing borate, a nitrile compound, and a propanesulfonic acid pyridinium salt. In some embodiments, the first additive comprises at least one of vinylene carbonate (VC), tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, succinonitrile, adiponitrile, glutaronitrile, and hexanetrinitrile.

[0046] In some embodiments, based on the mass of the electrolyte, the mass percentage of the first additive is 0.05% to 10%. In some embodiments, the mass percentage of the first additive can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5% or a range consisting of any two of these values. In some embodiments, the mass percentage of the first additive is 0.1%-5%.

[0047] In some embodiments of the present disclosure, the secondary battery provided by the present disclosure includes a negative electrode plate, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material of the negative electrode active material layer includes a silicon-based material, or includes a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium.

[0048] In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon oxides, and silicon carbon compounds. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. In some embodiments, the tin-based material includes at least one of tin, tin oxide, and tin alloys. In some embodiments, the phosphorus-based material includes phosphorus and / or phosphorus-carbon composites.

[0049] In some embodiments, the mass percentage of the silicon-based material is 10% to 100% based on the mass of the negative electrode active material.

[0050] In some embodiments, the negative electrode active material is selected from silicon, silicon monoxide and / or a silicon-carbon composite.

[0051] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding of the negative electrode active material particles to each other and to the current collector.

[0052] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, and the like.

[0053] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0054] In some embodiments, a negative electrode sheet of the present disclosure includes a negative electrode active material, a binder, and a conductive agent.

[0055] In some embodiments, the negative electrode active material of the present disclosure may also be selected from other materials that can electrochemically absorb and release metal ions such as lithium ions. Specifically, it can be selected from carbonaceous materials, silicon materials, alloy materials, lithium-containing metal oxide materials, etc. They can be used alone or in any combination of two or more.

[0056] In some embodiments, the negative electrode sheet further includes a negative electrode current collector, which can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0057] In some embodiments, the secondary battery provided by the present disclosure further includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, and the positive electrode active material of the positive electrode active material layer includes at least one of lithium nickel transition metal oxide and phosphate.

[0058] In some embodiments, the lithium nickel transition metal oxide comprises LiNi x Co y M (1-x-y) O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1.

[0059] In some embodiments, the phosphate comprises LiMn k B (1-k) PO4, 0≤k≤1, and the B element includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead.

[0060] In some embodiments, the positive electrode active material is selected from lithium nickel transition metal oxides.

[0061] In some embodiments, the positive active material may have a coating on the surface, or may be mixed with another compound having a coating. In some embodiments, the coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous or crystalline. The coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.

[0062] In some embodiments, the positive electrode active material further includes a binder, and optionally a conductive agent. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.

[0063] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0064] In some embodiments, the positive electrode active material includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0065] In some embodiments, the positive electrode plate further includes a positive current collector, which may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.

[0066] In some embodiments, the secondary battery and device of the present disclosure are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the device of the present disclosure are not particularly limited, and can be any technology disclosed in the prior art.

[0067] In some embodiments, the isolation film includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0068] In some embodiments, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.

[0069] Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0070] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0071] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0072] The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).

[0073] In some embodiments, the secondary battery disclosed herein is a lithium-ion battery.

[0074] In some embodiments, the secondary battery involved in the present disclosure includes the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0075] In some embodiments, the secondary battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0076] In some embodiments, the shape of the secondary battery is not particularly limited, and it may be cylindrical, square, or any other shape.

[0077] In some embodiments, the present disclosure further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present disclosure uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0078] In some embodiments, the present disclosure further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0079] Device:

[0080] The present disclosure also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack.

[0081] In some embodiments of the present disclosure, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.

[0082] In some other embodiments of the present disclosure, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0083] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.

[0084] Examples and Comparative Examples

[0085] Embodiment 1:

[0086] (1) Preparation of electrolyte: In an argon-protected glove box (water content <1 ppm, oxygen content <1 ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.35% of amyl nitrite was added to the total mass of the electrolyte. Then, lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and the mixture was stirred evenly to obtain the lithium ion battery electrolyte of Example 1.

[0087] (2) Preparation of positive electrode sheet: The positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive carbon black and binder polyvinylidene chloride are mixed, and the mixture is dispersed in N-methylpyrrolidone (NMP) to obtain positive electrode slurry, and then the positive electrode slurry is evenly coated on both surfaces of the aluminum foil, and after drying, calendering and vacuum drying, the positive electrode sheet is obtained.

[0088] (3) Preparation of negative electrode sheet: Mixed silicon-carbon material, conductive carbon black, binder (styrene-butadiene rubber, polyacrylic acid) and sodium carboxymethyl cellulose in a mass ratio of 96.0:1.0:2.4:0.6, and disperse the mixture in deionized water to obtain negative electrode slurry. The negative electrode slurry is coated on both surfaces of copper foil, and after drying, rolling and vacuum drying, a compaction density of 1.50 g / cm 3 The desired compaction density can be obtained by adjusting the conventional technical means in the art, such as controlling the rolling pressure, rolling temperature, rolling speed, etc. of the electrode sheet.

[0089] (4) Preparation of lithium-ion batteries: A three-layer separator with a thickness of 11 μm is placed between the above positive electrode and negative electrode sheets (a single layer of 2 μm boehmite-containing inorganic coating is applied on opposite sides of a 9 μm polyethylene PE base film), and then a sandwich structure consisting of the positive electrode sheet, the separator and the negative electrode sheet is laminated, and then placed in an aluminum-plastic film packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid, and the above-prepared electrolyte is injected into the battery cell, which is vacuum-sealed and left to stand at room temperature for 12 hours and at a high temperature of 45°C for 12 hours.

[0090] (5) Formation: Charge at 0.05C for 120 minutes, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, formation is complete, stand at high temperature for 24 hours, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, and capacity division is completed.

[0091] Embodiment 2:

[0092] The steps of Example 2 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.4% of isobutyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 2 is obtained after stirring evenly.

[0093] According to the steps in Example 1, a compacted density of 1.6 g / cm 3 The negative electrode.

[0094] Embodiment 3:

[0095] The steps of Example 3 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.8% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 3 is obtained after stirring evenly.

[0096] According to the steps in Example 1, a compacted density of 1.65 g / cm 3 The negative electrode.

[0097] Embodiment 4:

[0098] The steps of Example 4 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.2% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 4 is obtained after stirring evenly.

[0099] The compacted density was 1.7 g / cm 3 The negative electrode.

[0100] Example 5

[0101] The steps of Example 5 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.5% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 5 is obtained after stirring evenly.

[0102] The compacted density was 1.63 g / cm 3 The negative electrode.

[0103] Example 6

[0104] The steps of Example 6 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 1% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 6 is obtained after stirring evenly.

[0105] The compacted density was 1.95 g / cm 3 The negative electrode.

[0106] Example 7

[0107] The steps of Example 7 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 3% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 7 is obtained after stirring evenly.

[0108] The compacted density was 2.55 g / cm 3 The negative electrode.

[0109] Example 8

[0110] The steps of Example 8 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then ethyl nitrite is added to account for 0.5% of the total mass of the electrolyte, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 8 is obtained after stirring evenly.

[0111] The compacted density was 1.55 g / cm 3 The negative electrode.

[0112] Example 9

[0113] The steps of Example 9 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 0.3% of propyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 9 is obtained after stirring evenly.

[0114] According to the steps in Example 1, a compacted density of 1.4 g / cm 3 The negative electrode.

[0115] Example 10

[0116] The steps of Example 10 are the same as those of Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then butyl nitrite is added to account for 5% of the total mass of the electrolyte, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Example 10 is obtained after stirring evenly.

[0117] The compacted density was 2.75 g / cm 3 The negative electrode.

[0118] Comparative Example 1:

[0119] (1) Preparation of electrolyte: In an argon-protected glove box (water content <1 ppm, oxygen content <1 ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L. After stirring evenly, the lithium ion battery electrolyte of Comparative Example 1 was obtained.

[0120] (2) Preparation of positive electrode sheets: The positive electrode ternary high nickel active material, conductive carbon black and binder polyvinylidene chloride are mixed in a mass ratio of 97.5:1.5:1.0, and the mixture is dispersed in NMP to obtain a positive electrode slurry. The positive electrode slurry is then evenly coated on both surfaces of an aluminum foil, and the positive electrode sheet is obtained after drying, calendering and vacuum drying.

[0121] (3) Preparation of negative electrode sheet: Mixed silicon-carbon material, conductive carbon black, binder (styrene-butadiene rubber, polyacrylic acid) and sodium carboxymethyl cellulose in a mass ratio of 96.0:1.0:2.4:0.6, and disperse the mixture in deionized water to obtain negative electrode slurry. The negative electrode slurry is coated on both surfaces of copper foil, and after drying, rolling and vacuum drying, a compaction density of 1.5 g / cm 3 The desired compaction density can be obtained by adjusting the conventional technical means in the art, such as controlling the rolling pressure, rolling temperature, rolling speed, etc. of the electrode sheet.

[0122] (4) Preparation of lithium-ion batteries: A three-layer separator with a thickness of 11 μm was placed between the above positive electrode and negative electrode (a single layer of 2 μm boehmite-containing inorganic coating was applied on opposite sides of a 9 μm polyethylene PE base film), and then a sandwich structure consisting of the positive electrode, the separator and the negative electrode was laminated, and then placed in an aluminum-plastic film packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid. The above-prepared electrolyte was injected into the battery cell, and vacuum-sealed, and allowed to stand at room temperature for 12 hours, and then allowed to stand at a high temperature of 45°C for 12 hours.

[0123] (5) Formation: Charge at 0.05C for 120 minutes, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, formation is complete, stand at high temperature for 24 hours, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, charge at 0.1C to 4.2V, discharge at 0.2C to 2.5V, and capacity division is completed.

[0124] Comparative Example 2:

[0125] The steps of Comparative Example 2 are the same as those of Comparative Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=10:20:5:40, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Comparative Example 2 is obtained after stirring evenly.

[0126] The compacted density was 1.6 g / cm 3 The negative electrode.

[0127] Comparative Example 3:

[0128] The steps of Comparative Example 3 are the same as those of Comparative Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Comparative Example 3 is obtained after stirring evenly.

[0129] The compacted density was 1.7 g / cm 3 The negative electrode.

[0130] Comparative Example 4:

[0131] The steps of Comparative Example 4 are the same as those of Comparative Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 2% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Comparative Example 4 is obtained after stirring evenly.

[0132] The compacted density was 1.65 g / cm 3 The negative electrode.

[0133] Comparative Example 5

[0134] The steps of Comparative Example 5 are the same as those of Comparative Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then 4.5% of amyl nitrite of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Comparative Example 5 is obtained after stirring evenly.

[0135] The compacted density was 2.55 g / cm 3 The negative electrode.

[0136] Comparative Example 6

[0137] The steps of Comparative Example 6 are the same as those of Comparative Example 1, except that, in the preparation of the electrolyte: in an argon-protected glove box (water content <1ppm, oxygen content <1ppm), fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are mixed in a mass ratio of FEC:EC:PC:DEC=5:20:5:55, and then ethyl nitrite accounting for 5.5% of the total mass of the electrolyte is added, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and the lithium ion battery electrolyte of Comparative Example 6 is obtained after stirring evenly.

[0138] The compacted density was 1.55 g / cm 3 The negative electrode.

[0139] Test method:

[0140] 1. Cycle capacity retention rate test:

[0141] At 25°C, the prepared lithium-ion secondary battery was charged to 4.2V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 500 times by the above method, and the discharge capacity was recorded each time. The capacity retention rate of the lithium-ion secondary battery after 500 cycles at 25°C = the discharge capacity of the 500th time / initial discharge capacity × 100%.

[0142] 2. Current DC impedance test method:

[0143] The battery that has been cycled for 100 cycles in the cycle capacity retention test is adjusted to the target SOC with a current of 0.33C, left to rest for 30 minutes, and the voltage V0 at this time is recorded as the OCV of the corresponding SOC. The battery is discharged for t seconds using a discharge current I1, and the voltage V1 at the tth second is recorded. The DCR is calculated using the calculation formula for the discharge DC internal resistance: DCR = (V0-V1) / I1.

[0144] 3. Test method for negative electrode compaction density:

[0145] Compacted density test of negative electrode: disassemble the battery cell to obtain the electrode, wash off the electrolyte with DMC solution and prepare the sample. Use a tablet press to cut out 10 to 15 pieces with an area of ​​1540.25mm 2 The weight of the small disc is M (the average weight of 10 to 15 small discs is taken), the unit is mg, the thickness is H (the average value is measured at 15 points with a micrometer), the unit is mm, and then the conductive layer is wiped off, the weight of the current collector is m (the average weight of 10 to 15 small discs is taken), the unit is mg, the thickness is h, the unit is mm, and the compaction density PD is (Mm) / ((Hh)×1540.25), the unit is g / cm 3 .

[0146] The lithium ion batteries of Examples 1 to 10 and Comparative Examples 1 to 6 were subjected to electrochemical tests, and the obtained data are shown in Table 1.

[0147] Table 1

[0148]

[0149]

[0150] Comparison of Examples 1 to 10 and Comparative Examples 1 to 6 shows that by controlling the amount of the nitrite additive and the compaction density of the negative electrode sheet, the SEI component on the surface of the negative electrode sheet can be adjusted, thereby adjusting the wettability of the surface of the negative electrode active material particles to the electrolyte, satisfying the condition -0.4≤Y-1.1194×X 3 +4.0598×X 2 Embodiments 1 to 10 with -5.1657×X+2.0564≤0.4 can effectively improve the battery cycle capacity retention rate and reduce the impedance DCR during the cycle. It can be seen from comparative examples 1 to 3 that in the absence of the addition of nitrite compounds and the above relationship is not satisfied, the battery cycle capacity retention rate decreases and the impedance DCR increases during the cycle. It can be seen from comparative examples 4 to 6 that even if a nitrite additive is added and its content meets the preset value, the content of the nitrite additive and the compaction density of the negative electrode sheet do not meet the above relationship, which will lead to a decrease in the cycle capacity retention rate; at the same time, due to the excessive addition of nitrite compounds, its DC impedance DCR increases significantly.

[0151] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present disclosure, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. A secondary battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and an electrolyte; the electrolyte includes a nitrite additive as shown in Formula I: Wherein R1 is selected from fluorine-substituted or unsubstituted C 1-11 Alkyl, fluorine-substituted or unsubstituted C 1-8 Alkoxy, fluorine-substituted or unsubstituted C 2-6 Alkenyl, fluorine-substituted or unsubstituted C 2-6 Alkenyloxy, fluorine-substituted or unsubstituted C 2-6 Alkynyl, fluorine-substituted or unsubstituted C 2-6 Alkynyloxy, fluorine-substituted or unsubstituted C 3-8 Cycloalkyl, fluorine-substituted or unsubstituted C 3-8 Oxiranyl or fluorine-substituted or unsubstituted C 6-12 Aryl; Based on the mass of the electrolyte, the mass percentage of the nitrite additive is Y%; the compaction density of the negative electrode plate is X g / cm 3 ; Where, -0.4≤Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564≤0.

4.

2. The secondary battery according to claim 1, characterized in that: -0.1≤Y-1.1194×X 3 +4.0598×X 2 -5.1657×X+2.0564≤0.1。 3. The secondary battery according to claim 1, characterized in that: 1.0≤X≤2.6; and / or, 0.01≤Y≤5.

4. The secondary battery according to claim 3, characterized in that: 1.4≤X≤2; and / or, 0.2≤Y≤3.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: R1 is selected from fluorine-substituted or unsubstituted C 1-6 Alkyl, fluorine-substituted or unsubstituted C 1-6 Alkoxy, fluorine-substituted or unsubstituted C 2-6 alkenyl or fluorine substituted or unsubstituted C 6-12 Aryl.

6. The secondary battery according to claim 5, characterized in that: The nitrite additive includes at least one of amyl nitrite, ethyl nitrite, propyl nitrite, butyl nitrite, isobutyl nitrite and hexyl nitrite.

7. The secondary battery according to claim 1, characterized in that: The negative electrode plate includes a negative electrode active material layer, the negative electrode active material of the negative electrode active material layer includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium; the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon-carbon compound, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the tin-based material includes at least one of tin, tin oxide and a tin alloy, and the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite; based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 10% to 100%.

8. The secondary battery according to claim 1, characterized in that: The positive electrode sheet comprises a positive electrode active material layer, wherein the positive electrode active material of the positive electrode active material layer comprises at least one of a lithium nickel transition metal oxide and a phosphate; the lithium nickel transition metal oxide comprises LiNi x Co y M (1-x-y) O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the phosphate includes LiMn k B (1-k) PO4, 0≤k≤1, and the B element includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead.

9. The secondary battery according to claim 1, characterized in that: The electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium (trifluoromethylsulfonyl) (perfluorobutylsulfonyl) imide, lithium bis (fluoromalonate) borate, lithium 4,5-dicyano-2-(trifluoromethyl) imidazole and lithium trifluoromethanesulfonate; the molar concentration of the lithium salt is 0.5 mol / L to 3 mol / L; and / or The electrolyte further comprises a solvent, wherein the solvent comprises at least one of a chain carbonate, a cyclic carbonate and a carboxylic acid ester; the chain carbonate is selected from at least one of dimethyl carbonate, fluorine-substituted dimethyl carbonate, diethyl carbonate, fluorine-substituted diethyl carbonate, dipropyl carbonate, fluorine-substituted dipropyl carbonate, ethyl methyl carbonate, fluorine-substituted ethyl methyl carbonate, methyl propyl carbonate, fluorine-substituted methyl propyl carbonate, ethyl propyl carbonate and fluorine-substituted ethyl propyl carbonate; the cyclic carbonate comprises at least one of ethylene carbonate, fluorine-substituted ethylene carbonate, propylene carbonate, fluorine-substituted propylene carbonate, butylene carbonate and fluorine-substituted butylene carbonate; the carboxylic acid ester is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorocarboxylic acid ester; and / or The electrolyte also includes a first additive, which includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate, a silyl-containing borate, a nitrile compound and pyridinium propanesulfonate; based on the mass of the electrolyte, the mass percentage of the first additive is 0.05% to 10%.

10. A device, characterized in that: The device comprises the secondary battery according to any one of claims 1 to 9.